Development of a SNP Panel for Geographic Assignment and Population Monitoring of Jaguars (Panthera onca) - Gabriele Zenato Lazzari; Henrique Vieira Figueiró; Caroline Charão Sartor; Emiliano Donadio; Sebastián Di Martino; Hope M. Draheim; Eduardo Eizirik (Ecology and Evolution)
ABSTRACT The jaguar (Panthera onca) is an iconic top predator that is threatened by habitat loss and fragmentation, along with an emerging expansion of poaching for the illegal trade of live individuals and their parts. To address the need for tools that improve surveillance and monitoring of its remaining populations, we have developed a genome‐enabled single nucleotide polymorphism (SNP) panel targeting this species. From a dataset of 58 complete jaguar genomes, we identified and selected highly informative SNPs for geographic traceability, individual identification, kinship, and sexing. Our panel, named “Jag‐SNP”, comprises 459 SNPs selected from an initial pool of 13,373,949 markers based on the inter‐biome FST, followed by rigorous filtering and addition of eight sex‐linked SNPs. We then randomly selected subsets of this panel and identified an 84‐SNP set that exhibited a similar resolving power. With both the 459‐SNP panel and its 84‐SNP subset, samples were assigned with 98% success to their biomes of origin and 65%–69% of them were assigned to within 500 km of their origin. Furthermore, ca. 10–18 SNPs within these panels were sufficient to distinguish individuals, whereas 6 sex‐linked SNPs perfectly separated males and females. We used whole‐genome data from an additional 18 jaguars to further test these panels, which provided insights into kinship relationships and allowed inference of geographic origin of samples collected outside the spatial scope of the original sample set. These results support the strong potential of these panels as an efficient tool for application in forensic, genetic, ecological, behavioral and conservation projects targeting jaguars.